PENGGUNAAN REFUTATION TEXT BERBANTUAN ALAT PERAGA UNTUK MEREMEDIASI MISKONSEPSI TENTANG FLUIDA DINAMIS DI SMA - Iskandar, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to know the effectiveness of using refutation text readings assisted simple props in remediating students’ misconceptions about fluid dynamics in Taruna Bumi Khatulistiwa Senior High School Kubu Raya. This research was a quasy experimental design with nonequivalent control group design. The sample was the students of class XI IPA 1 (N=33) as the experiment class 1 and XI IPA 2 (N=31) as the experiment class 2 were chosen by intact group. The instrument of data collecting used diagnostic test like multiple choices without reasons. The results showed that the percentage of students who misconception were 86.67% and 88.46% at pretest. There were declines in the number of students who misconception about 63.67% and 44.21%. Based on the Mann-Whitney U test, there was the significant difference of the number of students’ misconceptions between the class remediated Refutation text assisted using simple props and without using simple props ( -2.44; 0,05). Remediation effectiveness showed by DQM price about 63.67% and 44.21%. This research is expected can be the alternative to remediate students’ misconceptions especially in physics. Keywords: Remediation, Misconception, Refutation Text, Simple Props, Fluid Dynamics